Metallurgical Characterization of SS 316L Repurposed by Wire Plus Arc Additive Manufacturing - Duong Vu; Van Thao Le (International Journal of Engineering and Technology Innovation, 2023)
This research aims to analyze the microstructures and mechanical characteristics of stainless steel (SS) 316L repurposed by wire plus arc additive manufacturing (WAAM). The SS 316L wire is deposited on a SS 316 substrate, which can be repurposed. This deposited material underwent optical microscopy, X-ray diffraction, and tensile test, and the results indicate that it features cellular and columnar dendrites at the bottom and equiaxial grains at the top. The tensile strength of the interface region between the deposited material (DM) and the base material (BM) is the highest (559 ± 4.16 MPa vs. 510 ± 4.93 MPa in DM and 540 ± 2.65 in BM), indicating that the BM and the deposited layers are strongly bonded. All the results from the defect observation, microstructures, and mechanical characteristics confirm the potential of the WAAM process for repurposing.